The influence of neighboring countries on the democratic transition process in Libyan - ELBAROUNI, ELYAS (Sharwes Scientific Journal, 2024)
Libya, which constituted an exception in its "fluctuating" regional relations with neighboring countries, during the Gaddafi era, entered into an exception of another kind in the post-revolutionary period, due to the data of its turbulent internal situation, which ranges from the proliferation of weapons, clashes of a tribal nature, and a country suffering Political and security fragility. From the foregoing, the research problem is focused on: What is the impact of neighboring countries on the process of democratic transition in Libya? The study aims to identify the basic determinants of the relationship between the internal situation in Libya and the regional neighborhood, and to clarify the motives and reasons for the interest of neighboring countries in the events in Libya, and to show the coordination mechanisms of neighboring countries to support the democratic transition process in Libya, as well as to highlight the repercussions on the process of democratic transformation, and the researcher followed the inductive approach Descriptive, and critical analytical approach, in order to understand and study the impact of neighboring countries on the process of democratic transition in Libya. In order to reach the most important results represented in the fact that there are a number of mechanisms that these countries can rely on in coordination between them to confront the escalating threat of terrorism in Libya and support the process of democratic transition, by harnessing the tools they possess, through security and military coordination between two or more countries and moving from Through an Arab force to confront terrorism, and work on the need to consider the objectives of the existing international coalition to combat terrorism, as well as the mechanism of collective action through holding successive meetings and gatherings.